Understanding the Constraints and Optimization of Serum Immunofixation Electrophoresis and Serum Free Light Chains for Detecting Monoclonal Proteins: A Single-Center Experience - Shastri, Malvika; Malhotra, Pankaj; Kaur, Harvinder; Aggarwal, Ritu (Journal of Laboratory Physicians, 2023)
Introduction Serum immunofixation electrophoresis (SIFE) and serum free light chain (SFLC) assay are imperative investigations in diagnosis and follow-up of multiple myeloma (MM). SFLC assays are reported to have higher sensitivity than SIFE. However, discrepancies have been reported between them. The current study was aimed at assessing concordance and discordance between SIFE and SFLC results in MM.Methods A total of 450 observations of both SIFE and SFLC were obtained from treatment-naive and follow-up MM patients.Results One hundred and twenty-nine (28.7%) values were observed as discordant, that is, positive SIFE with normal SFLC ratio or negative SIFE with abnormal SFLC ratio (p-value < 0.00001). Proportion of discordance was higher in SIFE positive-SFLC normal cases than SIFE negative-SFLC abnormal cases. Discordance was more frequent in follow-up cases.Conclusion Negative SFLC alone may not be reliable for MM follow-up. Algorithm may be based on SFLC measurements on each follow-up till attainment of normal SFLC ratio. Once SFLC normalizes, follow-up may be done with SIFE. If SIFE is positive, further follow-up with SIFE may be initiated.
Keywords: serum immunofixation; serum free light chain; multiple myeloma; concordance; discordance